THE INFLUENCE OF SERVICE QUALITY AND PRICE ON PURCHASING DECISIONS AT MR. FOX RESTAURANT, SOUTH JAKARTA BRANCH - Riri Oktarini; Putri Nilam Kencana; Nur Rachmah Wahidah (International Journal of Economy, Education and Entrepreneurship, 2022)
This study aims to determine the effect of service quality on purchasing decisions, the effect of price on purchasing decisions, and the effect of service quality and price together on purchasing decisions. The method used in this study is a quantitative method with a descriptive approach, taking a sample of 100, with analytical methods namely validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, correlation coefficient, coefficient of determination, test hypothesis testing. t and f test. The results of the hypothesis testing research using the t statistical test for the service quality variable (X1) obtained a tvalue > ttable or (6.272 > 1.984) this is reinforced by a significance value of 0.000 <0.05, meaning that there is a positive and significant effect service quality on purchasing decisions. The t-test of the price variable (X2) obtained a value of tcount > ttable or (5.145>1.984) this was strengthened by a significance value of 0.000 <0.05, meaning that there was a positive and significant effect on price on purchasing decisions. Based on the results of simultaneous testing or f-test, the value of Fcount > Ftable or (26.871> 3.090) is also strengthened by a significance probability value of 0.000 <0.05, meaning that service quality and price together have a positive and significant effect on decisions. purchase. Based on the multiple linear regression equation testing that has been done, the results are Y = 16.348 + 0.367X1 + 0.244X2 which implies that service quality and price are in line with purchasing decisions so that they have a positive effect on purchasing decisions at Mr. Restaurant. FOX South Jakarta Branch. The correlation coefficient obtained is 0.597, there is a low level of relationship between service quality and price on purchasing decisions, then with the coefficient of determination obtained a value (Kd) of 0.357, which means that service quality has an influence contribution to purchasing decisions of 35.7%, while the remaining 64.3% is influenced by other factors not examined in this study